1999
DOI: 10.1111/j.1559-1816.1999.tb01389.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Defendant Ethnicity on Juries' Dispositions of Felony Cases1

Abstract: This research examined jury decisions in 317 noncapital felony cases in El Paso, Texas, and assessed the impact of juror ethnicity on jury trial outcomes. Results revealed that there was no relation between defendant ethnicity and the probability of conviction. Anglo American defendants, however, received sentences that were approximately twice as severe as Hispanic defendants. Sentences imposed by juries were significantly related to defendant ethnicity and type of crime for which they were tried. Sentences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 46 publications
1
42
2
Order By: Relevance
“…An early study examining sentencing differences according to the ethnic composition of juries found Hispanic-majority juries to be more punitive toward Caucasian defendants than Caucasian-majority juries (Daudistel, Hosch, Holmes, & Graves, 1999). On the other hand, sentences given to Hispanic defendants did not differ according to the ethnic composition of the jury (Daudistel et al, 1999).…”
Section: Jury Decision Making: Hispanics Compared With Caucasiansmentioning
confidence: 94%
“…An early study examining sentencing differences according to the ethnic composition of juries found Hispanic-majority juries to be more punitive toward Caucasian defendants than Caucasian-majority juries (Daudistel, Hosch, Holmes, & Graves, 1999). On the other hand, sentences given to Hispanic defendants did not differ according to the ethnic composition of the jury (Daudistel et al, 1999).…”
Section: Jury Decision Making: Hispanics Compared With Caucasiansmentioning
confidence: 94%
“…However, a number of well designed archival analyses have demonstrated robust effects of victim and defendant race on White jurors (e.g. Baldus, Woodworth, Zuckerman, Weiner, & Broffitt, 2001;Bowers, Steiner, & Sandys, 2001;Daudistel, Hosch, Holmes, & Graves, 1999). In addition, most prosecutors and defense attorneys are convinced that White jurors favor the prosecution in cases with Black defendants, and continue to select juries based on this conviction despite Supreme Court prohibitions against the practice (Batson v. Kentucky, 1986;Sommers & Norton, 2008).…”
Section: The Original ''Race Salience'' Effectsmentioning
confidence: 98%
“…Research indicates that race bias intrudes into the jury decision-making process (Ayres & Waldfogel, 1994;Baldus & Woodworth, 1998;Barnett, Brodsky, & Manning-Davis, 2004;Brewer, 2004;Daudistel, Hosch, Holmes, & Graves, 1999;De Genova, 2004;Demuth & Steffensmeier, 2004). Most of the focus has been on bias affecting African Americans Sommers, 2007), but there is a history of prejudice toward Latinos within the legal system as well (Haney Lopez, 2003;Logue, 2009;Luna, 2003;Perez, Hosch, Ponder, & Trejo, 1993;Ramos, 2001;Schuck, Lersch, & Verrill, 2004;Turner & Johnson, 2005;Valencia, Garcia, Flores, & Juarez, 2004).…”
Section: Latinos Legal Bias and Immigrationmentioning
confidence: 94%
“…There is a history of mistrust between the Latino community and the legal system (Haney Lopez, 2003;Valencia et al, 2004). Consequently, research has demonstrated less bias by Latino jurors based on defendant ethnicity , and Daudistel et al (1999) found that Latino jurors did not favor Latino defendants but gave longer sentences to Anglo defendants. Future studies should examine whether Latinos differ in terms of perceptions of culpability based on ethnic immigrant status and SES, given that bias against Latino immigrants by Latinos has been demonstrated (Diaz et al, 2011;Mendez, Bauman, & Guillory, 2012).…”
Section: Limitations and Future Directionsmentioning
confidence: 96%